Megatrends and mythologems of artificial intelligence topics in Western scientific discourse - Baturina, Irina V. (Izvestiya of Saratov University Philosophy Psychology Pedagogy, 2024)
Introduction. For fifty years, the topic of artificial intelligence has remained leading within a wide range of scientific fields. Theoretical analysis. Preliminary analysis of the Scopus database results from a rating of publication activity, in which social sciences occupy insider positions along with computer sciences and some other areas. From the 60s of the past century to the present, there has been an exponential growth of scientific publications containing the label “artificial intelligence” in titles, abstracts and keywords. Empirical analysis. The article attempts, based on elementary numerical indi cators and qualitative content analytics, to identify trends in the subject of artificial intelligence in Western social sciences, the evolution of key research areas, as well as the main mythologies of scientific discourse. Conclusion. The research is preceded by the hypothesis: social sciences, owing to the specification of discourse and the subject spectrum, contain “naturalized” mythologems associated with other discursive practices and refractive scientific and technical interpretations of the subject of study.